2019
DOI: 10.1038/s41467-019-09124-x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of high-sensitivity and adapting vision with a cone opsin

Abstract: Inherited and age-related retinal degenerative diseases cause progressive loss of rod and cone photoreceptors, leading to blindness, but spare downstream retinal neurons, which can be targeted for optogenetic therapy. However, optogenetic approaches have been limited by either low light sensitivity or slow kinetics, and lack adaptation to changes in ambient light, and not been shown to restore object vision. We find that the vertebrate medium wavelength cone opsin (MW-opsin) overcomes these limitations and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 64 publications
3
125
0
2
Order By: Relevance
“…In the RGCs displaying this property, firing rate could thus be switched between low and high states by sequential presentations of 405 and 525nm light. The diversity of RGC responses to light in the Lamplight retina is consistent with the established ability of the retinal circuitry to invert polarity and apply different temporal frequency filters during signal transfer, and with the outcome of other studies restoring photosensitivity to ON bipolar cells [21][22][23] .…”
Section: Using Lamplight To Restore Visual Responses To the Degeneratsupporting
confidence: 82%
See 1 more Smart Citation
“…In the RGCs displaying this property, firing rate could thus be switched between low and high states by sequential presentations of 405 and 525nm light. The diversity of RGC responses to light in the Lamplight retina is consistent with the established ability of the retinal circuitry to invert polarity and apply different temporal frequency filters during signal transfer, and with the outcome of other studies restoring photosensitivity to ON bipolar cells [21][22][23] .…”
Section: Using Lamplight To Restore Visual Responses To the Degeneratsupporting
confidence: 82%
“…Gi/o signalling is also involved in GIRK-independent synaptic silencing, inhibiting presynaptic neurotransmitter release 19,20 Optogenetic control over Gi/o-protein signalling could be provided by the family of animal opsins, which function as light sensitive G-protein coupled receptors (GPCRs). Indeed, naturally occurring Gi/o coupled opsins, such as Rod opsin, LWS and SWS cone opsin and the engineered Gi-coupled OptoXR (a mu-Opioid receptor-Rod opsin chimera), have already been used as optogenetic tools, mostly as a method of restoring visual responses in the degenerate retina [21][22][23] , but also to produce neural inhibition in the brain 24,25 . However, these rod and cone opsin-derived tools have a fundamental characteristic that limits the degree to which their activity can be controlled under heterologous expression: while they are activated by light, their deactivation relies on light-independent mechanisms whose activity is largely outside the experimenter's control.…”
Section: Introductionmentioning
confidence: 99%
“…Good preservation of the inner retina in Tvrm4 mice, an excellent model of RHO AD RP Type B1, offers the opportunity to test the efficacy of vision restoration on adult animals by optogenetic tools targeting ON BCs, that is, driving the expression of ChR2 (Lagali et al, ; MacĂ© et al, ), MAG460 (Gaub et al, ), ReaChR (Sengupta et al, ), ChrimsonR (Klapoetke et al, ), or naturally occurring retinal cone opsins (Berry et al, ). This is particularly important in view of the present difficulty to treat dominant (gain‐of function) mutations by gene therapy directed to PRs: maintenance of the inner retina for sometimes after total PR loss offers therapeutic opportunities that exploit second‐order and higher order neurons to restore vision.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical trials have shown that most animal opsins exhibit excellent light sensitivity but poor temporal responsivity, compared to microbial opsins (Lin et al, 2008;Cehajic-Kapetanovic et al, 2015). However, a recent study utilized an alternative animal opsin to achieve high light sensitivity and quick response kinetics, both of which are imperative for visual prostheses (Berry et al, 2019). An opsin-free approach incorporates small light-sensitive molecules, deemed photoswitches, that can be bound to specific cellular proteins, such as ion channels.…”
Section: Optogeneticsmentioning
confidence: 99%